2021
DOI: 10.1073/pnas.2103617118
|View full text |Cite|
|
Sign up to set email alerts
|

Chromosome 10q26–driven age-related macular degeneration is associated with reduced levels of HTRA1 in human retinal pigment epithelium

Abstract: Genome-wide association studies have identified the chromosome 10q26 (Chr10) locus, which contains the age-related maculopathy susceptibility 2 (ARMS2) and high temperature requirement A serine peptidase 1 (HTRA1) genes, as the strongest genetic risk factor for age-related macular degeneration (AMD) [L.G. Fritsche et al., Annu. Rev. Genomics Hum. Genet. 15, 151–171, (2014)]. To date, it has been difficult to assign causality to any specific single nucleotide polymorphism (SNP), haplotype, or gene within this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…A large part of our understanding in this regard comes from samples selected based on the absence of phenotypes traditionally associated with vitreoretinal disorders. But many (Zouache et al, 2020;Williams et al, 2021) have shown that defining retinal diseases using phenotype alone is not sufficient. The consequences of genetic mutations driving AMD is for instance often detected late in life; however, their effect on retinal and choroidal structures is likely to begin much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…A large part of our understanding in this regard comes from samples selected based on the absence of phenotypes traditionally associated with vitreoretinal disorders. But many (Zouache et al, 2020;Williams et al, 2021) have shown that defining retinal diseases using phenotype alone is not sufficient. The consequences of genetic mutations driving AMD is for instance often detected late in life; however, their effect on retinal and choroidal structures is likely to begin much earlier.…”
Section: Discussionmentioning
confidence: 99%
“… 119 , 128 , 129 An important issue to consider is that AMD-associated variants at chromosome 10q26 loci, where HTRA1 is located, have been shown to decrease HTRA1 expression, suggesting HTRA1 -overexpressing mice may not represent the role of HTRA1 in AMD pathobiology. 130 This is further supported by a recent article from the Hageman group showing that HtrA1 is specifically reduced as much as 50% in the RPE of humans with the ARMS2 risk allele. 130 This appears to be due to disruption of a cis-acting regulatory element within the ARMS2 locus further supporting that augmentation, not inhibition, of HTRA1 is a rational therapeutic approach for AMD patients with the 10q26 risk allele.…”
Section: Models Of Amdmentioning
confidence: 76%
“… 130 This is further supported by a recent article from the Hageman group showing that HtrA1 is specifically reduced as much as 50% in the RPE of humans with the ARMS2 risk allele. 130 This appears to be due to disruption of a cis-acting regulatory element within the ARMS2 locus further supporting that augmentation, not inhibition, of HTRA1 is a rational therapeutic approach for AMD patients with the 10q26 risk allele. 130 …”
Section: Models Of Amdmentioning
confidence: 76%
See 1 more Smart Citation
“…The HtrA1 protein functions as both a secreted serine protease and an extracellular chaperone [ 70 ], and cleaves a variety of extracellular matrix (ECM) proteins, proteoglycans and growth factors [ 71 , 72 ]. Evidence suggests that the biological and disease initiation events associated with AMD driven by risk at Chr10 are distinct from Chr1-directed AMD [ 51 , 73 ]. However, the observed mitigating effect of protective CFH-CFHR5 on ARMS2/HTRA1 risk indicates that therapeutic interventions targeting the complement system may potentially modulate risk on Chr10.…”
Section: Discussionmentioning
confidence: 99%